Caracterização dos aptâmeros D4 e R4 como ferramentas teranósticas no câncer de próstata - Fernández, Esther Campos (2022)
RNA-binding aptamers from prostate cancer cells were selected against the human prostate tumor cell line PC-3 by our research group in 2016. From one of the selected aptamers, the A4 aptamer, smaller DNA and RNA aptamers were designed and named D4 and R4, respectively. With the aim of validating the use of D4 and R4 aptamers in prostatic circulating tumor cells detection systems to assist, above all, in the diagnosis of prostate cancer from peripheral blood samples, this work presents the functional characterization of D4 and R4 and the identification of their potential molecular targets. Thus, this thesis is divided into three chapters. Chapter I presents a systematic review with a comprehensive description of aptamer applications in the prostate cancer area during the last decade to better understand its advances and perspectives. The systematic review was published in 2021. Chapter II presents the manuscript of a scientific article on the in silico, in vitro and ex vivo characterization of D4 and R4 aptamers to determine their clinical uses in the context of prostate cancer. Chapter III includes the content of a patent that was published in 2022 (BR102020013625-9 A2 and PTC/BR2021/050290) and developed during this doctorate. The patent was presented for the homologation of the qualification of this doctorate degree.